Respuesta :
Answer:
[tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = -3e^{-2x} (x + 1) + C[/tex]
General Formulas and Concepts:
Calculus
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Multiplied Constant]: [tex]\displaystyle \frac{d}{dx} [cf(x)] = c \cdot f'(x)[/tex]
Derivative Property [Addition/Subtraction]: [tex]\displaystyle \frac{d}{dx}[f(x) + g(x)] = \frac{d}{dx}[f(x)] + \frac{d}{dx}[g(x)][/tex]
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Integration
- Integrals
- [Indefinite Integrals] Integration Constant C
Integration Property [Multiplied Constant]: [tex]\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx[/tex]
U-Substitution
Integration by Parts: [tex]\displaystyle \int {u} \, dv = uv - \int {v} \, du[/tex]
- [IBP] LIPET: Logs, inverses, Polynomials, Exponentials, Trig
Step-by-step explanation:
Step 1: Define
Identify
[tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx[/tex]
Step 2: Integrate Pt. 1
- [Integrand] Rewrite [Factor]: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = \int {3(2x + 1)e^{-2x}} \, dx[/tex]
- [Integral] Rewrite [Integration Property - Multiplied Constant]: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \int {(2x + 1)e^{-2x}} \, dx[/tex]
Step 3: Integrate Pt. 2
Identify variables for integration by parts using LIPET.
- Set u: [tex]\displaystyle u = 2x + 1[/tex]
- [u] Basic Power Rule [Derivative Properties]: [tex]\displaystyle du = 2 \ dx[/tex]
- Set dv: [tex]\displaystyle dv = e^{-2x} \ dx[/tex]
- [dv] Exponential Integration [U-Substitution]: [tex]\displaystyle v = \frac{-e^{-2x}}{2}[/tex]
Step 4: Integrate Pt. 3
- [Integral] Integration by Parts: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \bigg( \frac{-(2x + 1)e^{-2x}}{2} - \int {-e^{-2x}} \, dx \bigg)[/tex]
- [Integral] Rewrite [Integration Property - Multiplied Constant]: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \bigg( \frac{-(2x + 1)e^{-2x}}{2} + \int {e^{-2x}} \, dx \bigg)[/tex]
Step 5: Integrate Pt. 4
Identify variables for u-substitution.
- Set u: [tex]\displaystyle u = -2x[/tex]
- [u] Basic Power Rule [Derivative Property - Multiplied Constant]: [tex]\displaystyle du = -2 \ dx[/tex]
Step 6: Integrate Pt. 5
- [Integral] Rewrite [Integration Property - Multiplied Constant]: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \bigg( \frac{-(2x + 1)e^{-2x}}{2} - \frac{1}{2} \int {-2e^{-2x}} \, dx \bigg)[/tex]
- [Integral] U-Substitution: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \bigg( \frac{-(2x + 1)e^{-2x}}{2} - \frac{1}{2} \int {e^{u}} \, du \bigg)[/tex]
- [Integral] Exponential Integration: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \bigg( \frac{-(2x + 1)e^{-2x}}{2} - \frac{e^{u}}{2} \bigg) + C[/tex]
- [u] Back-Substitute: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = 3 \bigg( \frac{-(2x + 1)e^{-2x}}{2} - \frac{e^{-2x}}{2} \bigg) + C[/tex]
- Factor: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = -3e^{-2x} \bigg( \frac{2x + 1}{2} + \frac{1}{2} \bigg) + C[/tex]
- Simplify: [tex]\displaystyle \int {(6x + 3)e^{-2x}} \, dx = -3e^{-2x} (x + 1) + C[/tex]
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Integration